2010
DOI: 10.1515/epoly.2010.10.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of chitosan-polyvinylalcohol electrospinning process by response surface methodology (RSM)

Abstract: Abstract:Response Surface Methodology (RSM) is a collection of statistical and mathematical techniques useful for developing, improving, and optimizing processes. RSM was used to model and optimize the electrospinning parameters for the spinning of blend CS/PVA nanofibers. In this study, chitosan (CS)/polyvinyl alcohol (PVA) blend solutions (CS (M w =1 X 10 6 ) in 2% acetic acid and PVA (M w =12 X 10 3 ) in deionized water) with different blend ratio ranging from 10/90 to 50/50 were electrospun. CS/PVA (25/75)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…As presented by researchers at dilute acetic acid (2%) an increase of applied voltage results in a reduction of fibre diameter while in the present work it was observed that concentrated acetic acid (90%) lead to the opposite trend (Figure ). With increasing the acetic acid concentration the solution surface tension reduced significantly.…”
Section: Resultssupporting
confidence: 54%
“…As presented by researchers at dilute acetic acid (2%) an increase of applied voltage results in a reduction of fibre diameter while in the present work it was observed that concentrated acetic acid (90%) lead to the opposite trend (Figure ). With increasing the acetic acid concentration the solution surface tension reduced significantly.…”
Section: Resultssupporting
confidence: 54%
“…These easily visible differences could be produced by sudden changes in chitosan chain structures during the processing. An interesting explanation was given by Gholipour et al [24]. They observed that increasing the chitosan content produces brittle fibers; also high viscosity of pure chitosan causes severe problems such that fibers cannot even be electrospun.…”
Section: Methodsmentioning
confidence: 99%
“…Chitosan/PVA nanofibers have been fabricated successfully by electrospinning of chitosan in the presence of PVA using 2 wt% acetic acid as a solvent at various weight ratios between the polymer partners . The chitosan/PVA fibrous mats manifest a good antibacterial activity against the Gram‐negative bacteria Pseudomonas aeruginosa and are non‐toxic towards rat fibroblast L929 cells.…”
Section: Chitosan‐containing Nanofibrous Materials With Antibacterialmentioning
confidence: 99%